Case report: Chronic inflammatory demyelinating polyradiculoneuropathy with severe central nervous system demyelination: a clinicopathological study - Beck, Goichi; Yamashita, Rika; Kawai, Makiko; Yamamura, Ryohei; Okuno, Tatsusada; Matsui, Misa; Toyooka, Keiko; Morii, Eiichi; Mochizuki, Hideki; Murayama, Shigeo (Frontiers in Immunology, 2024)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is an immune-mediated disease that mainly affects the peripheral nerves and nerve roots and typically presents with distal dominant motor and sensory disturbances as clinical symptoms. Central nervous system (CNS) demyelination with inflammation occurs infrequently in patients with CIDP. Here, we present a unique autopsy report of CIDP causing severe demyelination along the entire spinal cord. A Japanese woman exhibited progressive muscle weakness, muscle atrophy, sensory disturbances, and tremors in her upper and lower extremities, which began in her 60s. A nerve conduction study revealed a marked prolongation of distal latencies and very low or no compound muscle action potential amplitudes, and cerebrospinal fluid protein levels were prominently elevated. Following the diagnosis of CIDP, a combination of methylprednisolone pulse therapy, high-dose intravenous immunoglobulin therapy, and plasma exchange mildly improved her symptoms. The patient died of septic shock at the age of 74 years. Neuropathological examination revealed demyelinating lesions with inflammation in the peripheral regions of the anterior, lateral, and posterior funiculi along the entire spinal cord (from the cervical to the sacral cord), and axons and neurons were well preserved in these lesions. The nerve roots in the cervical and lumbar plexuses, cauda equina, sciatic nerve, and sural nerve showed prominent swelling and edema with infiltration of inflammatory cells. Many onion bulbs were visible in the fascicles of the sciatic and sural nerves. Our results suggest that demyelination with inflammation can occur in the CNS and peripheral nervous system in CIDP, especially in patients with specific conditions, such as severe intrathecal inflammation.